Electrodynamics of helical slowing structure with high-current electron beam - Buts, V.A.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 1999)
In most theoretical and experimental research, devoted to studying the interactions of beams with hybrid structures, the beam density is assumed small, therefore it does not change a structure of eigenwaves of electrodynamic system the beam interacts with. It is interesting to consider another limiting case, when the beam density is already so large, that natural oscillations of beam partiсles ( wb ) are more than frequency of electromagnetic waves exited by beam, and when the presence of beam significantly changes the slowing structure electrodynamics. Thus, we have carried out analytical investigation and numerical analysis for dispersion chracteristics and have found increments of instability of nonequilibrium system – annular electron beam in helical slowing structure for a beam of large density, when the frequency of beam natural oscillations is more than frequency of oscillations excited by him.